Foliar Organic Fertilizer Enhanced Growth, Yield and Carotenoid Content of Carrot Plants (Daucus carota L.) Cultivated in the Lowland. Issue 1 (November 2021) - Nikmatullah, A; Samudra, G G; Zawani, K; Muslim, K; Nairfana, I; Sarjan, M
Abstract: Carrot is an increasingly important root vegetable in Indonesia, and it is commonly served as cooked mixed-vegetables or consumed freshly as salads or juices. Therefore, development of eco-friendly cultivation technology, including in lowlands, is important to meet the increased demand. This research analysed growth and yield of carrot plant in lowland in response to foliar-organic-fertilization as well as characterized the quality, carotenoid and sugar contents as well as hardness of the taproot. A Randomized completely block design (an RCBD) experiments was conducted in Bagik Polak Village, Labuapi District of West Lombok Regency (at ca . 45 m above mean sea level/amsl) from June to October 2020. During the cource of the experiment, the carrot plants were treated with 6 concentration of foliar organic fertilizer, that were 0 ml/L (K0), 5 ml/L (K1), 10 ml/L (K2), 15 ml/L (K3), 20 ml/L (k4) dan 25 ml/L (K5). There was no chemical fertilization added to the plots, but chicken manure of 20 tons/ha was equally given to all treatments. Application of foliar organic fertilizer increased growth and yield of the carrot plant by increasing physiological responses of the carrot plant as shown by a decrease ratio of above to below ground biomass and increase in the leaf chlorophyll content. Interestingly, application of foliar organic fertilizer enhanced the sweetness, carotenoid contents of the carrot taproots compared to the control plants.